Serious Game Attributes for the Construction of a Hazard Identification Framework - Mohd, Norhazren Izatie; Ali, Kherun Nita; Ahmad Fauzi, Ahmad Faiz Azizi; Ebrahimi, Shirin Shafiei (International Journal of Interactive Mobile Technologies (iJIM), 2018)
In recent years gaming products have increasingly been used to enhance learning and training development in the academic and commercial sectors.  Gaming is an approach that applies technology to provide an almost real experience with interactive field training.  It is an approach that supports the theory of learning by doing with a real case scenario.  The purpose of this paper is to determine serious game attributes to support effective training using serious game approach.  Through systematic literature review on eleven selected articles, nineteen game attributes were identified.  Hence, based on the definition and description from the articles, text analyses were conducted to determine categories of attributes based on educational theories' perspectives.  This study adopted the deductive content analysis approach which 14 relevant research articles between 1994 and 2016 were identified from the Web of Science and SCOPUS databases.  It appears that serious game attributes according to the educational perspectives are being practised using various ideas, terms and concepts.   Hence, the findings can be justified that serious game attributes are important to enhance the effectiveness of training modules.  All these attributes will become part of the serious game framework for hazard identification training modules.  The target is to deliver effective and active training module to construction-related workers.